Hubungan Antara Flashsale, Content Marketing, Kepuasan Pelanggan dan Keputusan Pembelian Kembali - Khansa Chaerunnisa; Penny Rahmah Fadhillah; Siti Marhamah; La Diadhan Hukama; Zainal Zawir Simon (Universitas YARSI, 2024)
This study aims to test the effect of flash sales and content marketing on repurchase decisions with customer satisfaction as an intervening variable. The population is consumers who have purchased and repurchased Snacktok Bittersweet by Najla products in Jabodetabek. Data analysis used the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results indicate that flash sales and content marketing mediated by customer satisfaction can be used as a model that influences repurchase decisions, namely: (1) Flash Sale has a positive and significant effect on Repurchase Decisions, (2) Content Marketing has a positive and significant effect on Repurchase Decisions, (3) Flash Sale has a positive and significant effect on Customer Satisfaction, (4) Content Marketing has a positive and significant effect on Customer Satisfaction, (5) Customer Satisfaction has a positive and significant effect on Repurchase Decisions, (6) Customer Satisfaction can mediate Flash Sale on Repurchase Decisions, (7) Customer Satisfaction can mediate Content Marketing on Repurchase Decisions. In Islam, the sale of Snacktok Bittersweet by Najla is in accordance with Islamic law, namely, the principles of justice, honesty, transparency, and customer satisfaction.